SARANA AKOMODASI SEBAGAI PENUNJANG INDUSTRI PARIWISATA DI KOTA TIDORE KEPULAUAN - Rais A Yudian; Liliana Dewi (Jurnal Cakrawala Ilmiah, 2022)
Tourism accommodation is one of the important aspects in the development of the tourism industry. Therefore, every region must be able to ensure the availability of accommodation as a means of supporting tourism development. The accommodation in question such as guesthouses, homestays, bungalows, hotels, villas and other types of accommodation. The city of Tidore Islands is one of the areas that must pay attention to accommodation facilities to support its tourism industry. Therefore, this study reviews the availability of tourism accommodation in Tidore Islands City, how accommodation in Tidore Islands City Develops, and what the role of akomidasi in the tourism industry in Tidore Islands City. With the research method used is a descriptive qualitative method whose data source is taken from the results of interviews and observations. The results of this study show that accommodation is very instrumental in supporting the tourism industry in Tidore Islands City.